Up the infinite corridor : - Hapgood, Fred (Addison-Wesley Publishing Company, 1993)
An inside look at the engineering profession discusses the current research projects and the nerd culture of Massachusetts Institute of Technology, allowing readers to admire and appreciate the pioneering work of these all-too-often ridiculed scientists